Targeted metabolomics analysis of nucleosides and the identification of biomarkers for colorectal adenomas and colorectal cancer - Zheng, Weifang; Wang, Mingwei; Chai, Xiaoyin; Pan, Fuzhen; Xu, Meihui; Wang, Yingchen; Lan, Liuhao; Hu, Feiran; Zhang, Zhe; Chen, Zhu (Frontiers in Molecular Biosciences, 2023)
he morbidity and mortality of colorectal cancer (CRC) have been increasing in recent years, and early detection of CRC can improve survival rate of patients. RNA methylation plays crucial roles in many biological processes and has been implicated in the initiation of various diseases, including cancer. Serum contains a variety of biomolecules and is an important clinic sample for biomarker discovery. In this study, we developed a targeted metabolomics method for quantitative analysis of nucleosides in human serum samples by using liquid chromatography tandem mass spectrometry (LC-MS/MS). We successfully quantified the concentrations of nucleosides in serum samples from 51 healthy controls, 37 patients with colorectal adenomas and 55 patients with CRC. The results showed that the concentrations of N6-methyladenosine (m6A), N1-methyladenosine (m1A) and 3-methyluridine (m3U) were increased in patients with CRC, whereas the concentrations of N1-methylguanosine (m1G), 2'-O-methyluridine (Um) and 2'-O-methylguanosine (Gm) were decreased in patients with CRC, compared with healthy controls and patients with colorectal adenomas. Besides, the levels of 2'-O-methyluridine (Um) and 2'-O-methylguanosine (Gm) were lower in patients with colorectal adenomas than those in healthy controls. Interestingly, the levels of Um and Gm were gradually decreased from healthy controls to colorectal adenomas patients to CRC patients. These results revealed that the aberrations of these nucleosides was tightly correlated to colorectal adenomas and CRC. In addition, the present work will stimulate future investigations about the regulatory roles of these nucleosides in the initiation and development of CRC.